A Prospective Study of Urinary Prostaglandin E2 Metabolite, Helicobacter pylori Antibodies, and Gastric Cancer Risk. (11th April 2017) - Wang, Tianyi; Cai, Hui; Zheng, Wei; Michel, Angelika; Pawlita, Michael; Milne, Ginger; Xiang, Yong-Bing; Gao, Yu-Tang; Li, Hong-Lan; Rothman, Nathaniel; Lan, Qing; Shu, Xiao-Ou; et al.
Summary: Independent of Helicobacter pylori, increased PGE-M in urine is associated with gastric cancer. Higher PGE-M levels may indicate additional risk for gastric cancer even among individuals infected with the more virulent strains of H. pylori in East Asia. Abstract: Background: Previous studies suggest that a stable end-product of prostaglandin E2, the urinary metabolite PGE-M, is associated with colorectal cancer, and 1 study of relatively small sample size found an association with gastric cancer among women. In the present study we further investigate the PGE-M, Helicobacter pylori, and gastric cancer association. Methods: The present analysis included 359 prospectively ascertained gastric cancer cases and 700 individually matched controls from the Shanghai Women's and Men's Health Studies. Urinary PGE-M was measured by a liquid chromatography/tandem mass spectrometric method. Seropositivity to 15 H. pylori recombinantly expressed fusion proteins was detected by H. pylori multiplex serology. Results: Adjusting for H. pylori, increasing PGE-M was associated with higher risk of gastric cancer (quartile 4 vs 1: odds ratio [OR], 1.76 [95% confidence interval CI, 1.17–2.66], P trend = .004). This association remained after excluding those diagnosed within 2 years from sample collection (OR, 1.73 [95% CI, 1.12–2.65], P trend = .007). However it was no longer present among individuals with 10 or more years of follow-up (2–4.9 years: OR, 3.15 [95% CI, 1.11–8.91]; 5–9.9 years: OR, 2.23 [95% CI, 1.22–4.06]; ≥10 years: OR, 0.73 [95% CI, .31–1.70]). Compared to H. pylori –negative individuals with below-median PGE-M levels, H. pylori –positive individuals with above-median PGE-M levels had a 5-fold increase in the odds of gastric cancer (OR, 5.08 [95% CI, 2.47–10.43]). Conclusions: In China, higher PGE-M levels may indicate an increased risk of gastric cancer independent of the risk conferred by H. pylori infection status, particularly for cancers diagnosed within 10 years of sample collection.